A study on voltage sag in industry system with adjustable speed drive - Syahrul Ashikin, Azmi; Mohd Fayzul, Mohammed; Siti Rafidah, Abdul Rahim; Mohd Rafi, Adzman; Zainuddin, Mat Isa; Ismail, Daut, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by Universiti Malaysia Perlis (UniMAP), 15th - 16th March 2008 at Putra Palace, Perlis, Malaysia.